Scientific Bases of Rational Nutrition - Solieva Maftuna Gulomjonovna; Khasanova Dilfuza Yuldashalievna (Scientific Trends, 2023)
This article considers nutrition as the most important aspect of a healthy lifestyle. After all, it is thanks to proper and balanced nutrition that a person can provide himself with emotional and physical health. Nutrition is the main source of life for our body. Not the least place in importance is maintaining hygiene, which I am an integral part of a healthy lifestyle, because a clean body serves as a defense against many diseases and also provides an opportunity for better functioning of the body.
Keywords: functional, pathological, diet, protein, fat, carbohydrate, vitamin, mineral salts, enzyme, hormone, antibody, pituitary, glycogol (glycine), glutamic acid, serine, tyrosine, cystine (cysteine), alanine, proline, arginine, asparagine, histidine, lysine, methionine, tryptophan, phenylalanine, leucine, isoleucine, threonine, valine